Pseudopodium enriched atypical kinase 1(PEAK1) promotes invasion and of melanoma cells by activating JAK/STAT3 signals. Issue 1 (1st January 2021) - Pan, Min; Yin, Xiaohui; Huang, Yi-chuan
ABSTRACT: Pseudopodium enriched atypical kinase 1(PEAK1) is a non-receptor tyrosine kinase, which is enriched in the pseudopodia of migrating cells and plays an important role in regulating cell migration and proliferation. In the study, we investigate the therapeutic effect of PEAK1 on melanoma cells in vitro and in vivo . We used a lentiviral vector to express short hairpin RNAs (Lv-PEAK1 shRNA) for inhibiting PEAK1 expression in the melanoma SKMEL28 cells. A full-length PEAK1 gene was cloned into the pcDNA 3.1 (+) plasmid and used to infect the melanoma SKMEL19 cells. P6 (also known as Pyridines 6, EMD Chemicals), the Pan-JAK inhibitor, was used to inhibit the Janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3) pathway. The cell counting kit-8 (CCK-8), colony formation assay and transwell assay were used to detect cell proliferation, growth and invasion in vitro . The effect of PEAK1 on melanoma progression in vivo was also evaluated. Protein expression of PEAK1, E-cadherin, vimentin and JAK/STAT3 was measured using western blot assay or immunohistochemistry. The results showed that enforced PEAK1 expression facilitated melanoma cell growth, invasion and metastasis via activating JAK/STAT3 signals, and PEAK1 knockdown inhibited melanoma cell growth, invasion and metastasis via inactivating JAK/STAT3 signals. Further work demonstrated that P6 (500 nM) treatment reversed PEAK1-induced effect in melanoma cells. PEAK1 promotes tumorigenesis and metastasis via activating JAK/STAT3 signals, and PEAK1 knockdown reduced tumorigenesis and metastasis in melanoma via inactivating JAK/STAT3 signals, providing a novel therapeutic strategy for melanoma treatment.